ANALISIS PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi pada Perusahaan Consumer Goods yang terdaftar di BEI pada Tahun 2012-2016) - Ardiana, Erna; Chabachib, Mochammad (Faculty of Economics and Business Diponegoro University, 2018)
The company's goal is to maximize shareholder value as measured by the company's stock price that affects the value of the company. This study aims to analyze the factors that affect firm value (PBV) in consumer goods company that is listed on the Indonesia Stock Exchange period of 2012-2016. Independent variables used in study are capital structure (DER), firm size, liquidity (CR) and profitability (ROE) as an intervening variable.The population used in this study are all companies engaged in consumer goods company which is listed on Indonesia Stock Exchange (IDX) period of 2012-2016. Sampling in this study using purposive sampling which resulted in a sample into 30 companies of consumer goods sectors. The analysis technique used is Path Analyst which is a development of the bivariate and multiple regression analysis.The results of this study showed that firm size and liquidity have a positive effect and significant to profitability, capital structure has a negative effect and insignificant to profitability. Profitability and firm size have a positive effect and significant to firm value. Capital structure and liquidity have a positive effect and insignificant to firm value. Profitability is able to mediate the effect of firm size and liquidity on firm value. But profitability is not able to mediate the effect of capital structure on firm value.